2017
DOI: 10.1002/2017jc012849
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Induced Ocean Warming of the Antarctic Continental Shelf in an Eddying Global Climate Model

Abstract: Ocean warming near the Antarctic ice shelves has critical implications for future ice sheet mass loss and global sea level rise. A global climate model with an eddying ocean is used to quantify the mechanisms contributing to ocean warming on the Antarctic continental shelf in an idealized 2xCO2 experiment. The results indicate that relatively large warm anomalies occur both in the upper 100 m and at depths above the shelf floor, which are controlled by different mechanisms. The near‐surface ocean warming is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 67 publications
8
55
0
Order By: Relevance
“…Recent results demonstrate the important roles of these forcings in the cross‐ACS heat transport. We also expect the choice of a fixed isobath as the boundary of the coastal control volume to introduce some bias in the heat transport calculations, because it does not always record the heat transport across the moving ASF axis (as discussed by Goddard et al, , for their simulation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results demonstrate the important roles of these forcings in the cross‐ACS heat transport. We also expect the choice of a fixed isobath as the boundary of the coastal control volume to introduce some bias in the heat transport calculations, because it does not always record the heat transport across the moving ASF axis (as discussed by Goddard et al, , for their simulation).…”
Section: Discussionmentioning
confidence: 99%
“…The product u ( y , z , t ) θ ( y , z , t ) is accumulated at each model time step. However, since neither the quantity θ ( y , z , t ) − θ f ( y , z , t ) nor the product u ( y , z , t ) θ f ( y , z , t ) were saved, we follow Goddard et al () and set θ f to the minimum freezing temperature found along the 1,000‐m isobath in the simulation ( θ f =−2.64 ∘ C). This means that the quantity ρ C p [ θ ( y , z ) − θ f ] must be interpreted as an upper bound (i.e., warmest value) for the melting potential of the intruding water masses.…”
Section: The Cross‐shelf Break Heat Transport Along the Antarctic Conmentioning
confidence: 99%
“…While the surface wind stress plays a leading‐order role in determining the strength of the ASC, dense water formation on the shelf will also intensify lateral buoyancy gradients across the shelf break by increasing the density contrast with offshore water masses. This mechanism may be sensitive to changes in either the location or rates of sea ice formation, since brine rejection tends to mix dense waters throughout the water column, increasing the density at depths comparable to the offshore CDW (Goddard et al, ). In regions where the shelf fills with dense water, further production is balanced by the export of this dense water and a compensating onshore flow of lighter density classes that shoals the stratification at the shelf break.…”
Section: Structure and Regional Variations Of The Ascmentioning
confidence: 99%
“…Scientific focus on ASC eddies, and mesoscale variability in general, has intensified in recent decades largely due to their role in transporting heat across the Antarctic continental slope (e.g., Figures 3a–3c and Goddard et al, ; Stern et al, ; St‐Laurent et al, ). Initial modeling forays into this topic at relatively coarse resolution (∼4‐km horizontal grid spacing) detected CDW accessing the shelf via inertial overshoots , in which the slope current approaches a trough in the continental slope and continues onto the shelf via inertia (see Figure 3c; Dinniman et al, , ; Dinniman & Klinck, ).…”
Section: Dynamics and Variability Of The Ascmentioning
confidence: 99%
See 1 more Smart Citation